First test [compact disc, unabridged] : - Pierce, Tamora (Pierce, Tamora. Protector of the small., 2007)
Ten-year-old Keladry of Mindalen, daughter of nobles, serves as a page but must prove herself to the males around her if she is ever to fulfill her dream of becoming a knight. When Alanna became the King's Champion, it was decided that girls would henceforth be allowed to train for the knighthood. But ten years have passed, and no girls have come forward. Now, however, someone is about to change all that and her name is Kel.